Social Competences, Perceived Social Support on Boarding School Students’s Psychological Well-being Mediated by Adaptability - Shahab, Fitria; Idriyani, Natris (Psympathic : Jurnal Ilmiah Psikologi, 2025)
Adolescents in an excellent boarding school are facing high challenges and demands. The fulfillment of adolescents’ psychological well-being (PWB) enables the development of various competencies, supports the achievement of satisfactory outcomes, and contributes to healthier functioning in adulthood. Therefore, this study aimed to   determine the role of students’ ability to manage challenges and demands (adaptability) in mediating the relationship between social competence (SC, social and emotional skills including cognitive reappraisal, prosocial behavior, social efficacy, normative and social adjustment), perceived social support (PSS), and PWB. A quantitative method with a cross-sectional design was adopted with adopted. The participants were 402 students in Madrasah Aliyah Negeri (MAN) Serpong and Pekalongan, and a path analysis method was conducted with Smart-PLS. The result showed that adaptability mediated the influence of SC and PSS on the PWB. Furthermore, the study recommended that school need to provide programs to facilitate students’ adaptability through the development of positive PSS and improvement of SC.